Analisis Sentimen K-Popers di Twitter (X) terhadap Harga Tiket Konser Menggunakan Metode Support Vector Machine: Studi Kasus: Golden Disk Awards 2024 - Sri Sutjiningtyas; Samsul Budiarto; Marlyna Infryanty Hutapea; Nurulqolbi Mutmainnah (METHOMIKA: Jurnal Manajemen Informatika & Komputerisasi Akuntansi, 2025)
Korean Pop (K-Pop) in Indonesia has grown rapidly, creating a large and influential community of fans, known as “K-Popers”. The popularity of K-Pop is supported by digital technology that allows easy access to South Korean music and entertainment content. Social media, including Twitter (X), became the main platform for K- Pop fans or K-Popers to interact and share opinions about the South Korean music industry. The ticket price of The 38th Golden Disc Awards (GDA) 2024 in Jakarta became a controversial hot topic, causing debate among fans regarding the overpriced ticket price. This study aims to analyze the sentiment of K-Popers towards GDA 2024 ticket prices using the Support Vector Machine (SVM) method to classify positive and negative sentiments related to GDA 2024 ticket prices. The analysis showed that negative sentiment was more dominant with 62.31% of 2698 tweets, indicating the need to evaluate the ticket price policy by the organizers. Sentiment classification with SVM method achieved the highest accuracy of 85.19% with polynomial kernel at the proportion of training and test data of 90:10, indicating that this method is good at classifying positive and negative sentiments. This research provides insights for event organizers regarding fan responses and can help in planning ticket pricing policies and marketing strategies so as to increase subsequent customer satisfaction.